Graft Copolymerization of Acrylamide Monomer onto Kappa-Carrageenan and Determination of the Grafting Parameters - Soleimani, Fatemeh; Sadeghi, Mohammad; Shahsavari, Hadis (Asian Journal of Chemistry, 2012)
The polysaccharide, kappa-carrageenan (kC), has been chemically modified by graft copolymerization of acrylamide (AAm) in an aqueous medium using ceric ammonium nitrate as an initiator under argon atmosphere. Evidence of grafting was obtained by comparison of FTIR spectra of kappa-carrageenan and homopolymer-free kC-g-poly(AAm) as well as solubility characteristics and gravimetric analysis of the products. The optimum reaction conditions affording maximum grafting ratio and add-on value have been determined.